Blood Neurofilament Light Chain as a Biomarker of Central Network Dysregulation in Methamphetamine Use Disorder: A Multi‐Modal Investigation with Clinical Implications - Shyh‐Yuh Wei; Yu‐Li Liu; Huai‐Hsuan Tseng; Po See Chen; Yen Kuang Yang; Yihong Yang; Tzu‐Yun Wang (Psychiatry and Clinical Neurosciences, 2026)
Aim There is a critical need for objective biomarkers that can link peripheral assays to central neural network dysfunction. We investigated blood neurofilament light chain (NfL), a marker of axonal injury, and C‐reactive protein (CRP), a marker of systemic inflammation, in relation to the brain network topology and microstructural integrity in methamphetamine use disorder (MUD), a paradigm of acquired neurotoxicity. Methods Forty‐two male MUD patients and 44 male controls received diffusion and resting‐state functional magnetic resonance imaging and underwent analysis of blood NfL and CRP levels. Results Compared to controls, MUD patients exhibited significantly elevated blood NfL and CRP levels, as well as salience‐network dysfunction and microstructural abnormality. Furthermore, higher NfL levels were associated with lower local efficiency (segregation) in the right anterior insula and higher mean diffusivity in the right insula and supramarginal gyrus, supporting a link with axonal injury. By contrast, higher CRP levels were associated with integration‐related graph measures in the bilateral supramarginal gyrus, suggesting that systemic inflammation may also be relevant to salience‐network dysfunction in MUD. Crucially, the correlation involving NfL levels remained significant after controlling for the duration of methamphetamine use, and higher baseline NfL levels were significantly correlated with greater urine positivity rates during one‐year follow‐up. Conclusions Blood NfL was associated with both functional and microstructural abnormalities of the salience network and potentially associated with relapse vulnerability in MUD.